Impact of uterine balloon tamponade on the use of invasive procedures in severe postpartum hemorrhage. (12th April 2017) - Gauchotte, Emilie; De La Torre, Manuela; Perdriolle‐Galet, Estelle; Lamy, Catherine; Gauchotte, Guillaume; Morel, Olivier
Abstract: Introduction: The aim of this study was to assess the impact of tamponade when uterotonic agents fail, on the need for surgery or interventional radiology. Material and methods: All women who received sulprostone for postpartum hemorrhage were retrospectively compared over two periods [December 2008 to December 2010 without use of tamponade (period 1) and June 2011 to June 2013 with use of tamponade (period 2)] in the case of sulprostone failure (STROBE compliant retrospective cohort study). During period 2, interventional radiology or surgery was used only in the case of tamponade failure. Results: 165 women were included (74 for period 1, 91 for period 2). The rate of interventional radiology or surgery significantly decreased from period 1 (21 of 74 women, 28.4%) to period 2 (six of 91 women, 6.6%, p = 0.0003). The rate of assumed failure of uterotonic agents was higher for period 2: 22 of 74 women (29.7%) during period 1, and 41 of 91 (45.1%, p = 0.0439) during period 2. The success rate of tamponade was 92.1% (35 of 38 women). Conclusions: Although the efficacy of tamponade should be viewed in the light of its widespread use, our findings confirm that tamponade significantly reduces the need for interventional radiology or surgery for postpartum hemorrhage treatment.